An unusual case of superficial (Cutaneous) angiomyxomas - Akshaya Nagaraja; Keerthi Jampani; Srilakshmi Peddireddy; Yugandhar Inakanti; Vijayshankar Metikurke (Our Dermatology Online, 2014)
Cutaneous myxomas also called angiomyxomas are rare benign connective tissue tumours, composed of stellate cells, set in a loose mucoid stroma. These lesions have been recognized as part of Carney complex. We report a 12 year old boy affected by multiple Superficial Angiomyxomas without any other components of Carney complex.